Comparative economic systems - Schnitzer, Martin C. (South-Western College, 2000)
The world of the twentieth century. Market mechanisms and capitalism. Nonmarket mechanisms and socialism. Market and nonmarket mechanisms in developing economies. Toward a new world order.